Estimation of the total parasite biomass in acute falciparum malaria from plasma PfHRP2. - Dondorp, A; Desakorn, V; Pongtavornpinyo, W; Sahassananda, D; Silamut, K; Chotivanich, K; Newton, P; Pitisuttithum, P; Smithyman, A; White, N; Day, N (2005)
BACKGROUND: In falciparum malaria sequestration of erythrocytes containing mature forms of Plasmodium falciparum in the microvasculature of vital organs is central to pathology, but quantitation of this hidden sequestered parasite load in vivo has not previously been possible. The peripheral blood parasite count measures only the circulating, relatively non-pathogenic parasite numbers. P. falciparum releases a specific histidine-rich protein (PfHRP2) into plasma. Quantitative measurement of plasma PfHRP2 concentrations may reflect the total parasite biomass in falciparum malaria. METHODS AND FINDINGS: We measured plasma concentrations of PfHRP2, using a quantitative antigen-capture enzyme-linked immunosorbent assay, in 337 adult patients with falciparum malaria of varying severity hospitalised on the Thai-Burmese border. Based on in vitro production rates, we constructed a model to link this measure to the total parasite burden in the patient. The estimated geometric mean parasite burden was 7 x 10(11) (95% confidence interval [CI] 5.8 x 10(11) to 8.5 x 10(11)) parasites per body, and was over six times higher in severe malaria (geometric mean 1.7 x 10(12), 95% CI 1.3 x 10(12) to 2.3 x 10(12)) than in patients hospitalised without signs of severity (geometric mean 2.8 x 10(11), 95% CI 2.3 x 10(11) to 3.5 x 10(11); p < 0.001). Parasite burden was highest in patients who died (geometric mean 3.4 x 10(12), 95% CI 1.9 x 10(12) to 6.3 x 10(12); p = 0.03). The calculated number of sequestered parasites increased with disease severity and was higher in patients with late developmental stages of P. falciparum present on peripheral blood smears. Comparing model and laboratory estimates of the time of sequestration suggested that admission to hospital with uncomplicated malaria often follows schizogony-but in severe malaria is unrelated to stage of parasite development. CONCLUSION: Plasma PfHRP2 concentrations may be used to estimate the total body parasite biomass in acute falciparum malaria. Severe malaria results from extensive sequestration of parasitised erythrocytes.